Metabolome, microbiome, and gene expression alterations in the colon of newborn piglets with intrauterine growth restriction - Tang, Wu; Zhang, Wanghong; Azad, Md. Abul Kalam; Ma, Cui; Zhu, Qian; Kong, Xiangfeng (Frontiers in Microbiology, 2022)
Newborn animals with intrauterine growth restriction (IUGR) are characterized by impaired intestinal structure and function; however, their intestinal microbiota and metabolome profiles have not been fully identified. The present study investigated the differences in colonic microbiota, metabolomics, and barrier function-related gene expression profiles between the IUGR and normal birth weight (NBW) piglets at 7, 21, and 28 days of age. Forty-eight piglets from 24 litters were assigned to assess the differences in colonic microbiota, metabolomics, and gene expression between IUGR and NBW piglets. Compared with the NBW piglets, IUGR piglets had decreased Shannon index and increased Simpson index at 7 days of age, whereas a decreased Chao1 index at 21 days of age. The IUGR piglets had lower abundances of Firmicutes, Subdoligranulum, Ruminococcaceae_UCG-002, and Ruminococcaceae_UCG-003 at 7 days of age, and Bacteroidetes, Phascolarctobacterium, and Ruminococcaceae_UCG-005 at 21 days of age, when compared with the NBW piglets. Metabolomics analysis showed significant changes in 147 metabolites mainly involved in organic acids and their derivatives in the colon. Six different metabolic pathways were significantly enriched, including purine metabolism, amino sugar/nucleotide sugar metabolism, ubiquinone/other terpenoid-quinone biosynthesis, phenylalanine/tyrosine/tryptophan biosynthesis, phenylalanine metabolism, and histidine metabolism. Spearman correlation analysis further demonstrated significant correlations between colonic microflora and metabolites. In addition, colonic isobutyrate at 7 days of age and isovalerate and total short-chain fatty acids (SCFA) at 7 and 21 days of age, as well as acetate, propionate, butyrate, and total SCFA levels at 28 days of age, were lower in the IUGR piglets than in the NBW piglets. Furthermore, the mRNA expression of zonula occludens (ZO)-1 at 7 days of age, ZO-1, occludin, and interleukin (IL)-4 at 21 days of age were down-regulated in the IUGR piglets, whereas the tumor necrosis factor (TNF)-alpha at 21 and 28 days of age and nuclear factor-kappa B (NF-kB) at 28 days of age were up-regulated, when compared with the NBW piglets. The findings suggest that the IUGR pigs present abnormal microbiota and nutrient metabolism in the colon, which may further affect the intestine barrier function by regulating gene expression.